Analysis Of Statement Of Profit And Loss And Statement Of Cash Flows On Operating Cash Flow Ratio On Cv Biru Utama - Irma Herliza Rizki; Malkit Kaur (Institute of Computer Science (IOCS), 2022)
The purpose of this research is to analyze the Income Statement and Cash Flow Statement on the Operating Cash Flow Ratio on Cv Biru Utama. The research method used is quantitative. Data collection technique is to use secondary data. The population and sample in this study were 48 financial statements of CV. Main Blue, using saturated sampling technique. This study uses multiple linear regression analysis which first tested the classical assumption with normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing is done by F test and t test. The results showed that the Cash Flow Statement and the Profit and Loss Statement simultaneously had an effect on cash flow. The income statement has a significant effect on cash flow. The cash flow statement has a significant effect on cash flow